2019
DOI: 10.1177/1076029619845066
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Deep Vein Thrombosis in Patients With Pelvic and Acetabular Fractures

Abstract: This study aimed to investigate the incidence and risk factors for deep vein thrombosis (DVT) in patients with pelvic and acetabular fractures. Patients with pelvic or acetabular fractures were included. Demographic data, fracture classification, time to surgery, and d -dimer levels at admission and one day after surgical intervention were recorded. Duplex ultrasonography was performed in the lower extremities for DVT evaluation. All patients received mechanical and chemical thromboproph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 37 publications
(63 reference statements)
8
53
2
Order By: Relevance
“…In this study, although the increase of D-dimer was not found to be an independent risk factor for DVT, the postoperative D-dimer level of the DVT group was significantly higher than that of the non-DVT group, and the D-dimer test of almost all patients was positive. This is consistent with Wang et al’s view that D-dimer detection has poor specificity in trauma patients and its significance is limited [ 32 ]. Neither Tyagi et al nor we found the correlation between intraoperative tourniquet use and DVT, considering that short duration of tourniquet use could not significantly affect the blood status of lower extremities.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, although the increase of D-dimer was not found to be an independent risk factor for DVT, the postoperative D-dimer level of the DVT group was significantly higher than that of the non-DVT group, and the D-dimer test of almost all patients was positive. This is consistent with Wang et al’s view that D-dimer detection has poor specificity in trauma patients and its significance is limited [ 32 ]. Neither Tyagi et al nor we found the correlation between intraoperative tourniquet use and DVT, considering that short duration of tourniquet use could not significantly affect the blood status of lower extremities.…”
Section: Discussionsupporting
confidence: 92%
“…This result was not obtained in this study, which may be related to the small sample size and missed diagnosis of doctors in this single center study.Drinking history, advanced age,high-energy trauma, multiple injuries, and comminuted fracture are independent risk factors for DVT. Although these factors cannot be optimized, they are helpful for early identi cation of high-risk groups.D-dimer detection with high sensitivity and low speci city is mostly used to exclude patients with suspected VTE, and its increased level is related to the degree of trauma, fracture site, degree of in ammatory response, pregnancy, etc.In this study, although the increase of D-dimer was not found to be an independent risk factor for DVT, the postoperative d-dimer level of the DVT group was signi cantly higher than that of the non-DVT group, and the D-dimer test of almost all patients was positive.This is consistent with Wang's view that D-dimer detection has poor speci city in trauma patients and its signi cance is limited [28] .Neither Tyagi nor we found the correlation between intraoperative tourniquet use and DVT,considering that short duration of tourniquet use could not signi cantly affect the blood status of lower extremities.But Tyagi still believes that patients with higher VTE risk should consider using a tourniquet during surgery [29] .Whether this simple, low-cost, low-risk intraoperative method can reduce the risk of postoperative DVT remains to be further studied.The results showed that the average preoperative DVT formation was 6.55 ± 0.47 days after the trauma and 6.67 ± 0.48 days after the surgery, which may be related to the peak time of blood hypercoagulability. The d-dimer level reached its peak on the 1st and 7th days after the fracture surgery [30] .This study reviewed the changes in the types of DVT during the perioperative period,54.55% (6/11) complicated with distal thrombosis, 18.18% (2/11) complicated with proximal thrombosis, and 27.27% (3/11) complicated with mixed thrombosis.…”
Section: Discussionsupporting
confidence: 90%
“…Fractures of extremities are a well-known risk factor for venous thromboembolism. Especially patients suffering from pelvic fractures have a very high risk to develop deep venous thrombosis despite mechanical and pharmaceutical thromboprophylaxis [30]. Consequently, the four AIS subgroups (head, extremities, thorax, abdomen) were chosen to select an adequate number of confounding variables with clinical relevance in regard to the risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%